The use of active modified atmosphere for the conservation of minimally processed eggplant - Nasser, Mauricio D. [UNESP]; Mariano-Nasser, Flávia Aparecida C. [UNESP]; Borges, Cristine V. [UNESP]; Kovalski, Tânia Regina [UNESP]; Furlaneto, Karina Aparecida [UNESP]; Vieites, Rogério L. [UNESP] (FapUNIFESP (SciELO), 2018)
The aim of this work was to evaluate effects of different gas concentrations (O2 and CO2) on conservation of minimally processed eggplants. The eggplants were sanitized, processed and packed in nylon + transparent polyethylene. The vegetables were submitted to modified atmospheres (T1= atmospheric air; T2= vacuum; T3= 4% O2 and 5% CO2; T4= 4% O2 and 6% CO2; T5= 4% O2 and 7% CO2; T6= 4% O2 and 8% CO2). The minimally processed eggplants were kept at 5±1°C and 90±1% RH, for 10 days. After 0, 2, 4, 6, 8 and 10 days of storage, fresh weight loss, respiratory rate, color, soluble solids (SS), titratable acidity (TA), pH, SS/TA ratio, visual analysis and purchase intent were determined. We used completely randomized experimental design, in a factorial scheme 6x6 (atmosphere x days of conservation). The atmosphere with higher CO2 concentration (8%) reduced the respiratory rate more intensely. The minimally processed eggplant maintained at 4% O2 + 6% CO2 obtained better grades on the visual analysis and purchase intention, with 10-day storage period. The vacuum was not recommended to keep minimally processed eggplant refrigerated under the studied conditions.
Atmosfera modificada ativa na conservação de berinjela minimamente processada
Keywords: Quality; Solanum melongena; Storage